Study to improve the properties of polylactic acid by epoxidized crude rubber seed oil. Issue 6 (8th January 2020) - Thuy, Nguyen Thi; Nam, Bui Xuan; Duc, Vu Minh
Abstract: The polylactic acid plasticized by epoxidized crude rubber seed oil (EcRSO) was prepared by using a Brabender mixer to improve the ductility of polylactic acid (PLA). The weight ratios of PLA/EcRSO were changed from 100/0 to 90/10. The tensile properties proved that the addition of EcRSO to PLA led to a strong increase in elongation at break (815 %) and a very strong increase in tensile toughness (1370 %), but a decrease in tensile strength. The plasticization of PLA with EcRSO lowered the Tg as well as cold‐crystallization temperature. The initial weight loss temperature grew from 261.8 to 308.8 o C and the weight loss at 380 o C of PLA reduced from 90.9 to 83.2 % with the presence of 5 wt.% EcRSO. Based on the overall results of this investigation, EcRSO could be used as an environmental friendly plasticizer to replace petroleum‐based plasticizers in improvement the overall properties of PLA.